(untitled) (Jurnal Wicara Desa, 2024)
Muncan Village, Central Lombok Regency is one of the villages where the majority of its hamlets are furniture industry centers. Based on demographic data from the population, Muncan Village is a village where the majority of residents work as furniture entrepreneurs. The results of this furniture business produce by-products, namely wood sawmill waste. This sawmill waste has not been utilized by residents. This community service aims to provide information to the residents of Muncan Village about whether sawmill waste can be used to make horta (horticultural) dolls as decoration or tourism educational packages and briquettes as a tool for baking which later, if developed, will increase the income of the residents of Muncan Village. Kopang District, Central Lombok Regency. This community service was carried out on Saturday, February 3 2024 with the theme "Optimizing Village Potential for Tourism Development in Muncan Village". There are 2 methods of community service, namely community education methods and training methods. This community training has been able to increase the knowledge of mothers, even fathers and teenagers in Muncan Village in making horta dolls and briquettes. Proven by the increase in questionnaire scores from 0.01% before community service to more and less 50%.